Behind the Scenes of Central Bank Digital Currency : Emerging Trends, Insights, and Policy Lessons - Soderberg, Gabriel (International Monetary Fund, 2022)
Central banks are increasingly pondering whether to issue their own digital currencies to the general public, so-called retail central bank digital currency (CBDC). The majority of IMF member countries are actively evaluating CBDCs, with only a few having issued CBDCs or undertaken extensive pilots or tests. This paper shines the spotlight on the handful of countries at the frontier in the hope of identifying and sharing insights, lessons, and open questions for the benefit of the many countries following in their footsteps. Clearly, what can be gleaned from these experiences does not necessarily apply elsewhere. The sample of countries remains small and country circumstances differ widely. However, the insights in this paper may inspire further investigation and allow countries to gain time by building on the experience of others. Importantly, the purpose of this paper is not to evaluate the courses taken by different jurisdictions, but to study and discuss their key experiences and lessons. The paper studies six advanced CBDC projects, drawing on collaboration and exchanges with the respective central banks to get insights beyond what has previously been published. Unless a specific published source is cited, all information stems from interviews and workshops with members of CBDC project teams in each jurisdiction.